Analisis Pengendalian Kualitas Line Produksi Body Inner K56 dengan Tahapan DMAIC di PT. KMIL (Kurnia Mustika Indah Lestari) - Helena Sitorus; Gunawan Ferdiansyah (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2020)
One of the products of PT. Kurnia Mustika Indah Lestari is the inner body of K56. In one month the product rejects amounted to 2.0%, which exceeds the tolerance limit set by the company, namely 0.5%. It is necessary to carry out research aimed at determining the root of the dominant problem that causes rejection of the inner K56 body and determining the quality improvement proposal. The method used is quality control with the DMAIC stage. The results of the research findings show that the dominant root cause of reject burry is that work instructions are not carried out (Method) and working in a hurry to quickly rest (Human). The reject scratch type is due to lack of skill (Method) and pursuing a lot of rest time (Human). The recommendation to improve the quality of the reject burry is to carry out work instructions, be more careful when loading the material into the dies, always clean the inside of the dies, checkman supervises the manpower of the production process so that it works according to cycle time. For the reject scratch type, it is to provide training for man power, give warning instructions for the placement of parts while running the process, set rules for working times that are not too fast, take advantage of spare time to clean the machine. Keywords: Quality, Reject, DMAIC (Define, Measure, Analyze, Improve, Control).